2018
DOI: 10.1016/j.foodcont.2017.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Multiple fish species identified from China's roasted Xue Yu fillet products using DNA and mini-DNA barcoding: Implications on human health and marine sustainability

Abstract: Roasted fish fillet (Fig.1) represents a popular snack food in China and a preliminary analysis of the label found only fish common names, without any reference to a particular species (Table 1). Since there is still not a harmonization around the definition of these common names in China, retailers are thus induced to mislabel roasted fish fillet products for lucrative profits. This study used direct sequencing method based on fragments of 16S rRNA gene and subsequent BLAST analysis to investigate the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 74 publications
2
45
0
Order By: Relevance
“…Efficiency of PCR amplification is an important factor in the evaluation of DNA barcoding regions . Recent work showed that ITS (or ITS2) can be used for species identification and discrimination between authentic and substitute/adulterant plants .…”
Section: Resultsmentioning
confidence: 99%
“…Efficiency of PCR amplification is an important factor in the evaluation of DNA barcoding regions . Recent work showed that ITS (or ITS2) can be used for species identification and discrimination between authentic and substitute/adulterant plants .…”
Section: Resultsmentioning
confidence: 99%
“…As it has been widely discussed (Teletchea et al , ; Rasmussen & Morrissey, ; Böhme et al , ), both nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) are suitable for fish species identification. Although the limitation in the applicability of quantitative approaches has been highlighted (Mohamad et al , ; Amaral et al , ), mtDNA is still preferentially chosen as the target in many studies for qualitative analysis (Prado et al , ; Taboada et al , ; Xiong et al , ), due to the advantages of high mutation rate, multi‐copy nature and maternal inheritance. Moreover, the candidate gene marker should have a high inter‐specific variability and display either low or no intra‐specific variations (Teletchea et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Fish species authentication in the marketplace has become an international concern, mainly due to the widely reported species adulteration, where expensive or high‐demand species is replaced by a cheaper or more readily available one (Miller & Mariani, ; Ferrito et al , ; Xiong et al , ; Kim et al , ; Sultana et al , ; Xiong et al , ; Zeng et al , ; Sánchez et al , ). In particular, substitution of fish species in processed fish products is substantial, with an average prevalence rate of 30% in a recent investigation (ranging from less than 5% to 100%) (Pardo et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations